(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
E-Governance is about using advanced Information and Communications Technology (ICT) to improve and support all process in the governmental domain and provides government information and services to the citizens or businesses or government agencies through the Information Communications and Technology (ICT). E-Services include better delivery of government services less waste, greater accountability, greater accessibility, and public control via access to knowledge, decline in time and energy, revenue generation and cost savings to the citizens. This paper reviews the e-Governance services that are provided in the various departments and the steps taken by the Government of India to computerize the systems of Government to Citizen (G2C), Government to Business (G2B), and Government to Government (G2G).